Penapisan Genotipe Jarak Pagar (Jatropha curcas L.) untuk Toleransi terhadap Kekeringan - , Misnen; Endah Retno Palupi; Muhamad Syukur; , Yudiwanti (Indonesian Journal of Agronomy, 2012)
The selection of Jatropha curcasfor drought tolerance is one of the key points prior to growing the species extensively on marginal lands. The objective of this study was to determine drought tolerant genotypes based on morphological and physiological characters. The research consisted of two experiments. The first experiment was aimed at determining the moisture content of the media to generate drought stress. The experiment was arranged in a split-plot design with moisture content as the main plot and genotypes as sub-plot. Four level of moisture contents were tested, i.e. 22-23%, 27-28%, 32-33%, and 37-38%. The genotypes tested (9) were Dompu-1, Gunung Tambora, Bima (representing genotypes from dry areas); Aceh Besar, IP-2P, Komering (representing genotypes from wet areas); and IP-1M, Papua, Yogyakarta (representing genotypes from moderately dry areas). The result showed that 22-23% moisture content of the media was suitable for drought tolerance test in Jatropha curcas. The second experiment was screening of genotypes using the suitable media moisture content from first experiment. Twenty three genotypes were screened for drought tolerance under 22-23% media moisture content. The result show that Dompu-2, Indralaya and China were tolerant to drought; Sukabumi-1, Sukabumi-2, Pidi, Lahat, Kupang, Lampung-2, Lampung-3, Sumba, IP-2M, and IP-2A genotypes were moderately tolerant; Curup, Bogor-1, Bogor-2, Bogor-3, Pontianak, Pagar Alam, Palembang, Saweli, Jeneponto, and Medan genotypes were sensitive to drought. Plant height, leaf water content, leaf area and percentage of plant survival can be used as indicators of drought tolerance for seedling selection using a non-destructive method.Keywords: drought tolerance, genotypes, Jatropha curcas, screening